2013
DOI: 10.1111/jan.12202
|View full text |Cite
|
Sign up to set email alerts
|

The role of team climate in the management of emotional labour: implications for nurse retention

Abstract: The establishment of a strong team climate may help nurses to manage the emotional demands of their role, promote their well-being and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 107 publications
(181 reference statements)
7
80
0
4
Order By: Relevance
“…Even more so, people can form groups that are not work teams, e.g., societies and clubs, which require different measurements of climate. In sum, the direct approach so far only applies to specific teams and is hence mostly applied in organizational work team research (Anderson & West, 1998;Cheng et al, 2013;Zhu et al, 2016).…”
Section: Direct Approachmentioning
confidence: 99%
“…Even more so, people can form groups that are not work teams, e.g., societies and clubs, which require different measurements of climate. In sum, the direct approach so far only applies to specific teams and is hence mostly applied in organizational work team research (Anderson & West, 1998;Cheng et al, 2013;Zhu et al, 2016).…”
Section: Direct Approachmentioning
confidence: 99%
“…This suggested that nurses, who display higher levels of surface acting, also reported experiencing higher levels of interaction stress. Similarly, Cheng et al (2013) reported that surface acting (in the form of faking unfelt emotions) has a significant negative influence on the quality of care as perceived by patients. Chou et al (2012) also found that surface acting is positively related to emotional exhaustion, whilst also being negatively related to job satisfaction.…”
Section: The Effect Of Emotional Labour and Shift Work On Pwbwmentioning
confidence: 99%
“…In step two, based on previous research, the most salient component of emotional labour related to well-being in nurses, i.e. surface acting (Cheng, 2013, Chou, 2012, was included in the model. In step three the total score of the measure of the PESW was entered, in addition to the other predictors already in the model (model 3).…”
Section: Predictors Of Psychological Wellbeing At Workmentioning
confidence: 99%
“…The processes described generally suggest that a heavy workload, which is at the root of many of the problems noted, is associated with a high level of stress, lower job satisfaction and an increased likelihood that nurses will leave their jobs . Other studies have found links between job satisfaction and turnover intention and between supervisor and organizational support (Brunetto et al, 2013) and co-worker relationships (Cheng et al, 2013;Tourangeau and Cranley, 2006). A study by O'Brien-Pallas and colleagues (2010) found that higher levels of role ambiguity and role conflict were associated with higher turnover rates.…”
Section: Literature Reviewmentioning
confidence: 99%